Endosulfan Analysis of Berau Delta Pond Soil - Syam, Sufriady; Adawiyah, Rabiatul; Basir (Universitas Islam Lamongan, 2025)
The aquaculture areas of Berau Regency are traditionally managed through a polyculture system involving tiger shrimp (Penaeus monodon) and milkfish (Chanos chanos) in the Berau Delta. Aquaculture practitioners commonly apply insecticides and herbicide at the start of the rearing period or post-harvest to control weeds along pond embankments and surrounding areas. These practices have contributed to endosulfan accumulation in pond soils over time and affect aquaculture productivity. Assessing endosulfan levels in soil is critical and may inform level of level of accumulation of the harmfull sibstance overtime. This study aimed to inform soil characteristics across different pond age categories, hypothesizing that soil quality declines with increasing cultivation duration. The research was conducted within the operational aquaculture cycle, sampling soils from three ponds representing construction periods of 1990–2000, 2000–2010, and 2010–2020. Laboratory analysis revealed that pond soils in the Berau Delta did not contain detectable levels of endosulfan, with all samples showing concentrations below the limit of quantification (LoQ) of 0.040 mg/kg.